Saponins: Research Progress and Their Potential Role in the Post-COVID-19 Pandemic Era - Daniel Mieres-Castro; Freddy Mora-Poblete (MDPI AG, 2023)
In the post-COVID-19 pandemic era, the new global situation and the limited therapeutic management of the disease make it necessary to take urgent measures in more effective therapies and drug development in order to counteract the negative global impacts caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its new infectious variants. In this context, plant-derived saponins-glycoside-type compounds constituted from a triterpene or steroidal aglycone and one or more sugar residues-may offer fewer side effects and promising beneficial pharmacological activities. This can then be used for the development of potential therapeutic agents against COVID-19, either as a therapy or as a complement to conventional pharmacological strategies for the treatment of the disease and its prevention. The main objective of this review was to examine the primary and current evidence in regard to the therapeutic potential of plant-derived saponins against the COVID-19 disease. Further, the aim was to also focus on those studies that highlight the potential use of saponins as a treatment against SARS-CoV-2. Saponins are antiviral agents that inhibit different pharmacological targets of the virus, as well as exhibit anti-inflammatory and antithrombotic activity in relieving symptoms and clinical complications related to the disease. In addition, saponins also possess immunostimulatory effects, which improve the efficacy and safety of vaccines for prolonging immunogenicity against SARS-CoV-2 and its infectious variants.